2009
DOI: 10.1530/eje-09-0399
|View full text |Cite
|
Sign up to set email alerts
|

Germline VHL gene mutations in Hungarian families with von Hippel–Lindau disease and patients with apparently sporadic unilateral pheochromocytomas

Abstract: Objective: Von Hippel-Lindau (VHL) disease is a hereditary tumor syndrome caused by mutations or deletions of the VHL tumor-suppressor gene. Germline VHL gene alterations may be also present in patients with apparently sporadic pheochromocytoma (ASP), although a wide variation in mutation frequencies has been reported in different patient cohorts. Design: Herein, we report the analysis of the VHL gene in Hungarian families with VHL disease and in those with ASP. Methods: Seven families (35 members) with VHL di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 50 publications
1
29
0
2
Order By: Relevance
“…13,14 Pheochromocytomas were only regarded as sporadic benign or sporadic recurring, if germ-line mutation in any candidate pheochromocytoma gene has been excluded. The diagnosis of neurofibromatosis type 1 was excluded by clinical examination.…”
Section: Mutation Analysismentioning
confidence: 99%
“…13,14 Pheochromocytomas were only regarded as sporadic benign or sporadic recurring, if germ-line mutation in any candidate pheochromocytoma gene has been excluded. The diagnosis of neurofibromatosis type 1 was excluded by clinical examination.…”
Section: Mutation Analysismentioning
confidence: 99%
“…A teljes kódoló szakasz PCR-t követő Sanger-szekvená-lással és MLPA-val *új generációs szekvenálással, validált génpanelek bevezetése indokolt AIP = aryl interacting protein; CDC73 = ciklindependenskináz-73; CDKN1B = ciklinfüggőkináz-inhibitor-1B; FH = fumarát-hidratáz; GCM2 = gliasejt hiányzó homológ-2; GOT2 = glutamin-oxálecetsav-transzamináz; KIF1B = a kinezincsalád 1B-tagja; MAX = MYC-hez kapcsolódó faktor-X; MDH2 = malát-dehidrogenáz-2; MLPA = multiplex ligatióspróba-amplifikáció; MTC = medullaris pajzsmirigyrák; NF1 = neurofibromatosis 1-es típusa; PHD2 = propil-hidroxiláz-domént tartalmazó fehérje-2; PTEN = foszfatáz-és tenzinhomológ; RET = transzfekció során újraszerve-ződő fehérje; SDHA = szukcinát-dehidrogenáz A-alegysége; SDHAF2 = szukcinát-dehidrogenáz AF2-alegysége; SDHB = szukcinát-dehidrogenáz B-alegysége; SDHC = szukcinát-dehidrogenáz C-alegysége; SDHD = szukcinát-dehidrogenáz D-alegysége; TMEM127 = transzmembrán-protein-127; VHL = von Hippel-Lindau csoportba, amelyhez szükséges MLPA-vagy valamilyen egyéb, géndózis kimutatására alkalmas módszer [22,23].…”
Section: Sdha Sdhaf2 Sdhb Sdhc Sdhd Fh Mdh2 Got2 Tem127 Maxunclassified
“…A hazai VHL-gén-eltérésekhez társuló klinikai manifesztációk ismertetésével kimutattuk, hogy az MLPAvizsgálat a hazai beteganyagban is mintegy 15%-kal nö-velte a genetikai pozitív esetek számát [22], valamint a Ser80Leu-génvariáns patogenitását is egy nagy létszámú család részletes feldolgozásával bizonyítottuk [21].…”
Section: Sdha Sdhaf2 Sdhb Sdhc Sdhd Fh Mdh2 Got2 Tem127 Maxunclassified
“…23 In 2010, a study in the Netherlands 24 analyzed mutations in 945 VHL families and found VHL type 1 families to have 43% missense mutations, 17% frameshift mutations, 13% nonsense, 9% splice, 8% inframe deletion/insertions, and 10% partial/complete deletions. Partial large gene deletions result in complete defect of protein function.…”
Section: Vhl Gene Mutationsmentioning
confidence: 99%
“…Partial large gene deletions result in complete defect of protein function. 11,23 In contrast, VHL type 2 is more likely associated with missense mutations affecting the protein-binding sites of the VHL protein. 11,23 This mutation was also found in the Netherlands family study where missense mutations were found in 83.5% of VHL type 2 families.…”
Section: Vhl Gene Mutationsmentioning
confidence: 99%